Thinking Outside the Circle: Reflections on Theory and Methods for School-Based Garden Research. Issue 2 (24th July 2017) - Clague, Liesa; Harrison, Neil; Stewart, Katherine; Atkinson, Caroline
Abstract : School-based gardens (SBGs) are contributing to improvements in many areas of education, including nutrition, health, connectedness and engagement of students. While considerable research has been conducted in other parts of the world, research in Australia provides limited understanding of the impact of SBGs. The aim of this paper is to give a reflective viewpoint on the impact of SBGs in Australia from the perspective of an Aboriginal philosophical approach called Dadirri . The philosophy highlights an Australian Aboriginal concept, which exists but has different meanings across Aboriginal language groups. This approach describes the processes of deep and respectful listening. The study uses photovoice as a medium to engage students to become researchers in their own right. Using this methodology, students have control over how they report what is significant to them. The use of photovoice as a data collection method is contextualised within the Aboriginal philosophical approach to deep listening. For the first author, an Aboriginal researcher (Clague), the journey is to find a research process that maintains cultural integrity and resonates with the participants by affirming that a culturally sensitive approach to learning is important.